Friends' Choice : 1975-1991. - South African National Gallery, Cape Town (Cape Town : South African National Gallery, 1992)
Anziska, Wendy ; Arnott, Lauryn ; Becker, Carl ; Beeton, Julia ; Botha, Hardy ; Brajtman, Nadine ; Breebart, Andrew ; Coetzer, Jacques ; Coplans, Peta ; Costello, Michael ; De Wet, Barend ; Dixon, Mark ; Ford, Simon ; Grandison, Sheila ; Green, Valerie ; etc.
Friends' Choice / Vriende se keuse : 1975-1991, An exhibition of works collected by the Friends of the SA National Gallery, South African National Gallery, Cape Town, 9 April 1992 - 2 May 1992
boek